Occurrence and role of Tph cells in various renal diseases - Junyi Ren; Kuai Ma; Xiangheng Lu; Haoyu Peng; Jia Wang; Moussa Ide Nasser; Chi Liu (BMC, 2024)
Abstract A new population of peripheral helper T (Tph) cells has been identified and contributed to various autoimmune diseases. Tph cells can secrete interleukin-21 (IL-21), interferon (IFN) and C-X-C motif chemokine ligand 13 (CXCL13) to moderate renal disease. Moreover, Tph cells can congregate in huge numbers and immerse within inflamed tissue. Compared to Tfh cells, Tph cells express high programmed cell death protein 1 (PD-1), major histocompatibility complex II (MHC-II), C-C chemokine receptor 2 (CCR2) and C-C chemokine receptor 5 (CCR5) but often lack expression of the chemokine receptor C-X-C chemokine receptor 5 (CXCR5). They display features distinct from other T cells, which are uniquely poised to promote responses and antibody production of B cells within pathologically inflamed non-lymphoid tissues and a key feature of Tph cells. In this review, we summarize recent findings on the role of Tph cells in chronic kidney disease, acute kidney injury, kidney transplantation and various renal diseases.